Performance, Space, Utopia - Jestrovic, S. author. aut Link
X, 226 p.
Keywords: Over 20 years after the war in Yugoslavia, this book looks back at its two most iconic cities and the phenomenon of exile emerging as a consequence of living in them in the 1990s. It uses examples ranging from street interventions to theatre performances to explore the making of urban counter-sites through theatricality and utopian performatives.